Pembuatan Video Animasi 3 Dimensi â€œKegiatan Pembelajaranâ€ Menggunakan Teknik Camera Tracking, Compositing dan Shading Sebagai Media Informasi Jurusan Teknik Komputer - Yolanda, Jefri; Ahmad Bahri Joni M; Meiyi Darlies (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
With advances in information and communication technology, the dissemination of information has become increasingly widespread and various different forms of delivery have been adopted. So with the development of information and communication technology, there are many ways to convey information about the Department of Computer Engineering. One of them is the delivery of information on the learning activities of the Computer Engineering Department. 3D animation video is an example of how to convey information that can be used by the Department of Computer Engineering. Also, by combining it with real life video, it can add a new impression to the information video for the Computer Engineering Department. Merging 3D animated videos with real life videos using camera tracking, compositing and shading techniques to make them more realistic. The development approach applied is the Villamil Mollina method. This involves careful planning, strong mastery of multimedia technology, and in-depth production management skills in creating 3-dimensional animated videos